Unveiling The Impact of Electronic Word-Of-Mouth On Corporate Social Responsibility Communication In The Banking Sector - Fauzan, Nizar; Kusumawati, Rita; Syahro Fitriyah, Nursaadah (International Journal of Management Science and Information Technology, 2023)
Corporate social responsibility (CSR) has become increasingly crucial for banking organizations to enhance competitiveness and financial success. This study investigates the impact of CSR communication on electronic word of mouth (eWOM), value co-creation, and the performance of Indonesian financial businesses. A research gap exists in understanding the specific effects of CSR communication in the Indonesian banking industry. The stratified sampling technique collects data from 150 customers aware of banking sector CSR initiatives. A questionnaire is administered via Google Forms and has the screening to gather relevant information. The survey data is analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). The results reveal that CSR communication significantly influences the CSR activities of Indonesian financial firms. CSR communication significantly affects Indonesian financial firms' electronic word-of-mouth (eWOM) activities. It positively influences eWOM, which in turn enhances value co-creation. Additionally, CSR communication has a significant impact on value co-creation. These findings highlight the importance of prioritizing CSR communication to improve the banking sector's competitive advantage and financial performance. Incorporating effective CSR communication into business strategies can enhance customer relationships, generate value, and improve all aspects. Understanding these dynamics can provide valuable insights for banks to optimize their CSR communication strategies, strengthen their impact on customers, and drive sustainable growth.